Melanocyte antigen‐specific antibodies cannot be used as markers for recent disease activity in patients with vitiligo. (10th March 2012) - Kroon, M.W.; Kemp, E. Helen; Wind, B.S.; Krebbers, G.; Bos, J.D.; Gawkrodger, D.J.; Wolkerstorfer, A.; van der Veen, J.P. Wietze; Luiten, R.M.
Abstract: Background  Objective parameters to assess disease activity in non‐segmental vitiligo are lacking. Melanocyte antigen‐specific antibodies are frequently found in the sera of patients with vitiligo and the presence of these antibodies may correlate with disease activity. Objective  To investigate the relationship between melanocyte antigen‐specific antibodies and recent disease activity in patients with vitiligo and to evaluate the potential usefulness of this objective parameter in daily clinical practice. Methods  The prevalence of tyrosinase, melanoma antigen recognized by T‐cells‐1 (MART1), melanin‐concentrating hormone receptor‐1 (MCHR1), gp100 and tyrosine hydroxylase (TH) antibodies was evaluated in 21 patients with non‐segmental vitiligo and in 20 healthy controls. Results  In 21 patients, nine (42.8%) showed antibody responses against tyrosinase, MART1, MCHR1, gp100 or TH. No antibody responses were found in the 20 controls. No correlation was found between the presence of antibodies and recent disease activity or other clinical characteristics such as age, gender, extension and duration of vitiligo. Conclusions  In this study, 42.8% of the vitiligo patients showed an antibody response to melanocyte antigen‐specific antigens. However, the presence of antibodies against melanocytes did not correlate with recent disease activity or other relevant disease parameters, and for the moment screening for these antibodies in individual patients does not appear to be clinically relevant.